Remarks on the derivation of the governing equations for the dynamics of a nonlinear beam to a non ideal shaft coupling - Fenili, André; Balthazar, José M. [UNESP]; Francisco, Cayo Prado Fernandes; Da Fonseca Brasil, Reyolando Manoel Lopes Rebello (AIP Publishing, 2014)
We derive nonlinear governing equations without assuming that the beam is inextensible. The derivation couples the equations that govern a weak electric motor, which is used to rotate the base of the beam, to those that govern the motion of the beam. The system is considered non-ideal in the sense that the response of the motor to an applied voltage and the motion of the beam must be obtained interactively. The moment that the motor exerts on the base of the beam cannot be determined without solving for the motion of the beam.